Pengaruh January Effect, Week Four Effect, Dan Holiday Effect: Studi Empiris pada Perusahaan LQ-45 yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Luth Fiana Afifatiningsih; Rr. Tjahjaning Poerwati (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2023)
Abstract This study aims to analyze the effect of January Effect, Week Four Effect, and Holiday Effect on Stock Return of LQ-45 companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. This study uses secondary data in the form of historical data taken from yahoofinance.com and IDX. Sampling was done by using purposive sampling method, resulting in 115 suitable samples based on predetermined criteria. The analytical method used to test the hypothesis in this study is multiple linear regression analysis. The results of the research that has been done show that the January Effect and Week Four Effect have no effect on Stock Returns, while the Holiday Effect has no effect on Stock Returns.   Keywords: January Effect, Week Four Effect, Holiday Effect, Stock Return